PENGARUH POSITIONING TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE LENOVO DI UNIVERSITAS BRAWIJAYA - Dzikrika, Dear Satriya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to analyze the influence of positioning on purchasing decisions Smartphone Lenovo in Brawijaya University . To find out how much influence the dependent variable (buying decisions) to the independent variables (Attribute, Benefit, and Price ). This study uses multiple regression analysis with SPSS version 17.0. This data collection method uses a questionnaire to consumer of Smartphone Lenovo in Brawijaya University.. Questionnaires were distributed 50 questionnaires. The results of studies using multiple linear regression analysis, showed that simultaneous variabel attribute (X1), benefit (X2), and price (X3), has a significant influence on buying decisions (Y). While partial, variable price showed a significant effect on decision buying consumen. Keywords: Positioning, Attribute, Benefit, Price, and Purchase Decision.